PERANCANGAN ULANG UI/UX PADA APLIKASI SAVE MONEY MENGGUNAKAN METODE HUMAN CENTERED DESIGN - Trisandi; Zaman, Baizul; H, Syamsul Bhahri (STMIK KHARISMA Makassar, 2025)
This research aims to redesign the UI/UX of the save money application. Data collection was carried out using the Human Centered Design (HCD) method. The data testing process uses the System Usability Scale (SUS) method developed by researchers and involving 30 respondents. After the evaluation is carried out, respondents are asked to answer the questions asked in the questionnaire and the results are used as a basis for drawing conclusions. In this research, the author redesigned the UI/UX of the save money application to make it easier for users to manage their finances. The test results using the System Usability Scale (SUS) method produced an average score of 79. So the results of the interpretation of the System Usability Scale (SUS) from SUS are between 68 - 80.3, so the grade is B with an adjective rating, namely Good.